Quantum twisting microscopy of phonons in twisted bilayer graphene - Birkbeck, J.; Xiao, J.; Inbar, A.; Taniguchi, T.; Watanabe, K.; Berg, E.; Glazman, L.; Guinea, F.; von Oppen, F.; Ilani, S. (Nature (London), 2025)
The coupling between electrons and phonons is one of the fundamental interactions in solids, underpinning a wide range of phenomena, such as resistivity, heat conductivity and superconductivity. However, direct measurements of this coupling for individual phonon modes remain a substantial challenge. In this work, we introduce a new technique for mapping phonon dispersions and electron–phonon coupling (EPC) in van der Waals (vdW) materials. By generalizing the quantum twisting microscope 1 (QTM) to cryogenic temperatures, we demonstrate its capability to map not only electronic dispersions through elastic momentum-conserving tunnelling but also phononic dispersions through inelastic momentum-conserving tunnelling. Crucially, the inelastic tunnelling strength provides a direct and quantitative measure of the momentum and mode-resolved EPC. We use this technique to measure the phonon spectrum and EPC of twisted bilayer graphene (TBG) with twist angles larger than 6°. Notably, we find that, unlike standard acoustic phonons, whose coupling to electrons diminishes as their momentum tends to zero, TBG exhibits a low-energy mode whose coupling increases with decreasing twist angle. We show that this unusual coupling arises from the modulation of the interlayer tunnelling by a layer-antisymmetric ‘phason’ mode of the moiré system. The technique demonstrated here opens the way for examining a large variety of other neutral collective modes that couple to electronic tunnelling, including plasmons 2 , magnons 3 and spinons 4 in quantum materials. Generalization of a quantum twisting microscope to cryogenic temperatures in twisted bilayer graphene shows the ability to map phononic dispersions through inelastic momentum-conserving tunnelling and reveals an angle-dependent coupling between electrons and phonons.